Research progress on heat shock transcription factors in insects - ZHANG Chao; WANG Ni; SHI Zheyi; CHEN Min; ZHOU Wenwu; ZHOU Ying; ZHU Zengrong (浙江大学学报. 农业与生命科学版, 2022)
Insects are capable of inducing the production of heat shock proteins when exposed to environmental stresses or under specific physiological conditions such as diapause. The transcriptional activation of heat shock proteins is usually controlled by the heat shock transcription factor (HSF), a class of transcription factors that are widely present in the organism. There are numerous HSF genes in plants and mammalian species, while previous studies suggested that many insects only had single HSF gene. Under normal conditions, HSF proteins are often present in the inactive form in cells, and they are activated upon shock, and then transferred to the nucleus, where they bind to specific functional domains of target genes and eventually activate the transcription of target genes to improve the tolerance of the whole organism. This paper reviewed the research progress on the basic structure, transcriptional regulation, and biological function of HSF in insects to deepen the understanding of the regulatory role of HSF in stress response mechanisms of insects, and provide new ideas for agroforestry pest control.